A bibliometric analysis of airport service quality. (September 2022) - Bakır, Mahmut; Özdemir, Emircan; Akan, Şahap; Atalık, Özlem
Abstract: Airports have evolved into key business centers in the last four decades, serving a variety of business models in addition to providing transportation infrastructure. Additionally, service quality, which is critical for airports to maintain a competitive edge, is a major area of research in the aviation literature. This study aims to analyze the existing literature on airport service quality through the bibliometric analysis method and to present a perspective on the literature's trajectory. Science mapping techniques and performance analysis were applied in this process. R-based Bibliometrix software was used to investigate 100 studies indexed in the Web of Science (WoS) database between 1975 and 2020. Research findings show that the Journal of Air Transport Management leads the literature in terms of publication performance. Researchers from China offer the highest contribution to the literature as a country. In addition, service quality research has largely resulted from collaboration networks. It is expected that an understanding of the research themes that emerge from the scientific mapping technique will guide researchers. Highlights: This study examines the airport service quality literature through a bibliometric analysis approach. Performance analysis and science mapping analysis are applied on 100 publications by employing the R bibliometrix package. Co-citation analysis shows the existence of three research clusters in the research area. The journal that contributes the most to the research area is JATM, and China is the most productive country.